Performance and efficiency of national innovation systems: lessons from the wine industry - Achille Amatucci; Vera Ventura; Dario Frisio (Wine Economics and Policy, 2024)
The multiplicity of factors involved in the innovation process makes its measurement and evaluation a complex endeavor. In this study we propose a new approach to measure and decompose the efficiency of national innovation systems in the wine industry considering the relationship between the innovation environment and economic performance. The analysis applies the data envelopment analysis approach to quantify the relative efficiency of each national system using a set of four indicators to describe the innovative environment in the wine industry as model inputs, and an index of international market performance as output. The results demonstrate a clear perspective of the innovation process within the wine industry, identifying the systems that efficiently use the available resources and those that encounter difficulties in translating innovation into economic performance. The proposed approach also captures the dynamics of the international innovation landscape in the wine industry, providing potential country-level strategies and opportunities to increase innovation systems’ efficiency.